Peran Guru dalam Penanganan Peserta Didik yang Bermasalah dengan Perilaku Anti Sosial Cyberbullying - Ubaidillah, Aan Eko Khusni (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2016)
At school, the teacher in charge as second parents for children. Unfortunately there are many teachers who do not live up to the philosophy of the teacher as second parents for children. There are still many teachers who abuse the students seemed never to have children. Even if the teacher does not live up to this philosophy, the teacher should be aware that he is under contract with parents to drop off their students to the gates of success. Reality on the ground there are many teachers who use violence. With disciplinary reasons, some unscrupulous teachers dare torment his students. Of course this makes children afraid to go to school and can not learn well. Fellow students bullying each other also because it is hard to emulate his teacher. Why do these problems arise? Therefore there are still persons who become teachers for material reasons only, not for the call. Including a teacher who was having psychiatric disorders, but not detected in the selection for work. The conclusion that acts of bullying become a global problem that must be addressed together by all parties. Picketing early through moral education, together with the full implementation of family life and responsibility, as well as the structuring law becomes effective the first step to reduce acts of bullying in society. Follow-settlement through legal means necessarily the final step after picketing failed to do and this is a little late to do because it would cause loss. All this should be carried out continuously by all parties without exception, from oneself, family, community, and country